The biology of developmental plasticity and the Predictive Adaptive Response hypothesis. (30th May 2014) - Bateson, Patrick; Gluckman, Peter; Hanson, Mark
Abstract: Many forms of developmental plasticity have been observed and these are usually beneficial to the organism. The Predictive Adaptive Response (PAR) hypothesis refers to a form of developmental plasticity in which cues received in early life influence the development of a phenotype that is normally adapted to the environmental conditions of later life. When the predicted and actual environments differ, the mismatch between the individual's phenotype and the conditions in which it finds itself can have adverse consequences for Darwinian fitness and, later, for health. Numerous examples exist of the long‐term effects of cues indicating a threatening environment affecting the subsequent phenotype of the individual organism. Other examples consist of the long‐term effects of variations in environment within a normal range, particularly in the individual's nutritional environment. In mammals the cues to developing offspring are often provided by the mother's plane of nutrition, her body composition or stress levels. This hypothetical effect in humans is thought to be important by some scientists and controversial by others. In resolving the conflict, distinctions should be drawn between PARs induced by normative variations in the developmental environment and the ill effects on development of extremes in environment such as a very poor or very rich nutritional environment. Tests to distinguish between different developmental processes impacting on adult characteristics are proposed. Many of the mechanisms underlying developmental plasticity involve molecular epigenetic processes, and their elucidation in the context of PARs and more widely has implications for the revision of classical evolutionary theory.